"Akademischer Nachwuchs": Reflections of a Veteran on a Strange Concept - Hanneder, Jürgen (Puṣpikā: Proceedings of the 12th International Indology Graduate Research Symposium (Vienna, 2021), 2023)
The German idea of “Akademischer Nachwuchs”, that is, young academics, is part of a structure built into our universities and based on a hierarchical teacher-student relationship. We know from Indological history that right from the beginning the often unpayed assistants contributed no less to the field than their well-payed superiors, and we also know from recent history that attempts to change some of the basic parameters of this system for the better came to naught. The lecture combines general thoughts on the topic with some personal observations, and a few historical examples from the early days of our subject.Keywords junior academics, teacher-student relationship, German Indology